NATURE+ in Vietnam - Report 2023 & Outlook 2024 - Naziri, Diego; Swaans, Cornelis; Jalonen, Riina (2023)
NATURE+ works in the north western Vietnamese provinces of Lao Cai and Son La. Known for their hilly terrain, terraced rice fields and diverse ethnic groups, these provinces have high potential for increased food production. But sustainability, nutrition, health, conservation of nature and traditional knowledge are sometimes overlooked. The Initiative aims to help address these gaps in the areas’ development.